Formulation and Application of EcoPlast Paving Block Based on LDPE Plastic Waste as Sustainable Construction Material for Pesantren Infrastructure - Ataya Syahira; Arina Zakyatul Putri; Fahmi Waladul Hafidz Al Huda; Vicky Wildan Yustisia (G-Tech: Jurnal Teknologi Terapan, 2026)
Indonesia generates an estimated 38.6 million tons of solid waste annually, with Low-Density Polyethylene (LDPE) forming a persistent fraction of plastic debris because it degrades extremely slowly in the environment. This study explores EcoPlast Paving Block, a cement-free paving element manufactured from shredded LDPE waste and natural sand, designed for the practical needs of Islamic boarding school (pesantren) infrastructure. Three LDPE–sand mass ratios (70:30, 50:50, and 40:60) were investigated, each represented by three specimens (n = 9) with nominal dimensions of 20 × 10 × 6 cm. Compressive strength was measured at 28 days, using the procedure of SNI 03-0691-1996 as an equivalent performance reference. The mixes achieved average strengths of 13.40 MPa, 20.54 MPa, and 42.69 MPa for 70:30, 50:50, and 40:60 respectively, indicating a consistent increase in strength with higher sand content and placing the 40:60 composition above the Grade A threshold. Water absorption remained below 3% for all specimens. These results suggest that LDPE–sand paving blocks can offer a lightweight, durable, and waste-based alternative to conventional cement paving in pesantren courtyards and access ways.